Representaciones sociales que sobre las rupturas amorosas en las relaciones de pareja, construyen un grupo de estudiantes de psicología - Muñoz Morcote, Fabian Andres (Universidad Antonio Nariño, 2024)
The present research aims to analyze the social representations that have 8 students of psychology, of which 4 are women and 4 are men against the romantic breaks in couples of young adults. With an analysis of 3 established categories of the theory of social representations: Beliefs, information and affective elements. Collecting the information for the half of the semi-structured interviews applied to the participants, allowing to identify the social representations that the participants have through the medium of the experience and the context in which they were developed.